Kajian Karakteristik Bentuk dan Isi Perda Tentang Bendega - Renhat Marlianus Siki (University of Udayana, 2018)
Bendega is a traditional institution in the field of maritime and fisheries on indigenous peoples in Bali in the coastal region, economic, social, cultural and religious that has historically continued to grow, evolving in accordance with the culture, and also the local wisdom of Bali. Bendega is one of three traditional institutions in Bali, namely, Desa Adat, Subak and Bendega. This purpose of this study to understand and interpret the characters of the form and character of the contents of the Bali Regional Regulation 11/2017 which are based on formal and material principles, and study settings using the method of thinking Regulatory Impact Assessment. This research used a normative research method. The results showed that the formation of the Bali Regulation 11/2017 was based on philosophical, sociological and juridical considerations. The establishment of the Bali Regulation 11/2017 is based on attribution authority and delegation. The content character of the Bali Regulation 11/20 is discretionary, in the sense of giving the Governor and the Regency / City Government the freedom of space. Bali Regional Regulation 11/2017 has addressed the character of responsiveness to pluralism in the legal order that applies in areas that have certainty and fulfill people's desires. The certainty of the rules of traditional socio-cultural and religious institutions in the field of fisheries which are part of the culture of traditional Balinese society. Furthermore, it is hoped that there will be a further scientific review of the Bali Provincial Regulations that have been stipulated in the Regional Gazette Bendega adalah lembaga tradisional di bidang kelautan dan perikanan pada masyarakat adat di Bali yang ada di wilayah pesisir, bersifat ekonomi, sosial, budaya dan religius yang secara historis terus tumbuh, berkembang sesuai dengan budaya dan kearifan lokal Bali. Bendega merupakan salah satu dari tiga lembaga tradisonal yang ada di Bali, yaitu, Desa Adat, Subak dan Bendega. Tujuan penelitian adalah memahami dan menginterpretasi karakter bentuk dan karakter isi Perda Bali 11/2017 yang berlandaskan pada asas formil dan materil, dan kajian pengaturan dengan menggunakan logika berpikir Regulatory Impact Assessment. Jenis penelitian ini adalah penelitian hukum normatif. Hasil penelitian menunjukan bahwa pembentukan Perda Bali 11/2017 adalah berdasarkan pertimbangan filosofis, sosiologis, dan yuridis. Pembentukan Perda Bali 11/2017 didasari pada kewenangan atribusi dan delegasi. Karakter isi Perda Bali 11/20 bersifat diskresioner, dalam pengertian memberikan ruang kebebasan kepada Gubernur dan Pemerintah Kabupaten/ Kota. Perda Bali 11/2017 telah menujukan karakter responsifitas terhadap kemajemukan tatanan hukum yang berlaku di daerah yang memiliki nilai kepastian dan memenuhi keinginan masyarakat. Kepastian aturan lembaga tradisional yang bersifat sosial budaya dan religius di bidang perikanan yang merupakan bagian dari budaya masyakat tradisional Bali. Untuk selanjutnya diharapkan adanya pengkajian ilmiah lebih lanjut tentang Perda-Perda Provinsi Bali yang telah ditetapkan dalam lembaran Daerah.